Hemiparasites can transmit indirect effects from their host plants to herbivores. Issue 2 (27th December 2017) - Haan, Nathan L.; Bakker, Jonathan D.; Bowers, M. Deane
Abstract: Parasitic plants can serve as critical intermediaries between their hosts and other organisms; however these relationships are not well understood. To investigate the relative importance of plant traits in such interactions, we studied the role of the root hemiparasite, Castilleja levisecta (Orobanchaceae), as a mediator of interactions between the host plants it parasitizes and the lepidopteran herbivore Euphydryas editha (Nymphalidae), whose caterpillars feed on Castilleja and sequester iridoid glycosides from it. We tested whether the hemiparasite's size, leaf N concentration, and iridoid glycoside concentrations were influenced by the identity of its host plant, and then whether these traits influenced outcomes for the herbivore. We found that the hemiparasite's size and leaf N depended on the host it parasitized, and these traits in turn affected outcomes for E. editha . Specifically, Euphydryas editha survival increased with hemiparasite size and caterpillar mass increased with leaf N; caterpillars with greater mass were more likely to survive during diapause. We also found preliminary evidence that host identity influenced iridoid glycoside sequestration by the herbivore. Mean iridoid glycoside concentrations in caterpillars ranged from 1–12% depending on the host being parasitized by Castilleja . This study demonstrates that root parasitism can result in strong indirect effects on higher trophic levels, influencing organisms' survival, growth, and chemical interactions.